A cross-chiral RNA polymerase ribozyme - Sczepanski, Jonathan T.; Joyce, Gerald F. (Nature (London), 2014)
Here, a cross-chiral RNA polymerase is developed—an RNA enzyme that can catalyse the templated polymerization of activated mononucleotides that are of the opposite handedness—shedding light on how RNA-based life could have emerged. An 'ambidextrous' ribozyme It is widely assumed that homochirality is a requirement for life and that biological macromolecules must be of the same stereochemical 'handedness' to interact efficiently. Working with Leslie Orgel and others, Gerald Joyce extended this idea in 1984 to suggest that homochirality may also be essential for the origins of life, as templated polymerization of RNA occurs readily in a homochiral system but is impaired in racemic mixtures. Now Joyce and co-author Jonathan Sczepanski show that RNAs of opposing chirality can work together. They devised a D -RNA enzyme that catalyses the polymerization of L -RNA on a L -RNA template — and vice versa. The catalytic potency of this ribozyme is sufficient for it to synthesize its own enantiomer by joining 11 component oligonucleotides. The ribozyme is thought to interact with its substrates via tertiary contacts rather than Watson–Crick base pairing. This unexpected finding will add a new dimension to thoughts on how life could have emerged in an 'RNA world'. Thirty years ago it was shown that the non-enzymatic, template-directed polymerization of activated mononucleotides proceeds readily in a homochiral system, but is severely inhibited by the presence of the opposing enantiomer 1 . This finding poses a severe challenge for the spontaneous emergence of RNA-based life, and has led to the suggestion that either RNA was preceded by some other genetic polymer that is not subject to chiral inhibition 2 or chiral symmetry was broken through chemical processes before the origin of RNA-based life 3 , 4 . Once an RNA enzyme arose that could catalyse the polymerization of RNA, it would have been possible to distinguish among the two enantiomers, enabling RNA replication and RNA-based evolution to occur. It is commonly thought that the earliest RNA polymerase and its substrates would have been of the same handedness, but this is not necessarily the case. Replicating d - and l -RNA molecules may have emerged together, based on the ability of structured RNAs of one handedness to catalyse the templated polymerization of activated mononucleotides of the opposite handedness. Here we develop such a cross-chiral RNA polymerase, using in vitro evolution starting from a population of random-sequence RNAs. The d -RNA enzyme, consisting of 83 nucleotides, catalyses the joining of l -mono- or oligonucleotide substrates on a complementary l -RNA template, and similar behaviour occurs for the l -enzyme with d -substrates and a d -template. Chiral inhibition is avoided because the 10 6 -fold rate acceleration of the enzyme only pertains to cross-chiral substrates. The enzyme’s activity is sufficient to generate full-length copies of its enantiomer through the templated joining of 11 component oligonucleotides.